Environmental Change and Sustainability 2013
DOI: 10.5772/55499
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Earth Observation and Satellite Information for Monitoring Desertification, Drought and Agricultural Activities in Developing Countries

Abstract: global average surface temperature has increased over the 20th century by about 0.6ºC [3]. Global Circulation Models have projected that this rise in temperature may increase to a range of 1.5-5.8ºC by the end of the century. Results of crop growth modeling under climate change scenarios suggest that agriculture, and thus human well-being, will be negatively affected by climate change, especially in developing countries [4]. The vulnerability to drought and land degradation has increased in the past decades an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Además de la distribución de la serie se trazó el modelo de tendencia lineal general (MLG) con sus correspondientes coeficientes. Estos resultados proporcionan una fuerte evidencia de que se registra una tendencia general a la baja del NDVI, concordante con las tendencias encontradas para la región pampeana (Zhao y Running, 2010;Samanta et al, 2011;Barbosa et al, 2013).…”
Section: Resultados Y Discusiónunclassified
“…Además de la distribución de la serie se trazó el modelo de tendencia lineal general (MLG) con sus correspondientes coeficientes. Estos resultados proporcionan una fuerte evidencia de que se registra una tendencia general a la baja del NDVI, concordante con las tendencias encontradas para la región pampeana (Zhao y Running, 2010;Samanta et al, 2011;Barbosa et al, 2013).…”
Section: Resultados Y Discusiónunclassified
“…This further suggests that either way there is a strong relationship between precipitation and abundance of vegetation as the trend revealed that a decrease in precipitation reflected a decrease in vegetation cover over the ecological zones. Therefore, the NDVI related to SPI are significant indicators for vegetation status and its response to precipitation variability [65].…”
Section: Drought Relationship To Ndvimentioning
confidence: 99%